Carbon Emissions Disclosure - Musta'in, Agung; Nurlisti, Izza; Maulana, Bayu Adam; Jubaedah, Siti (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The purpose of this study was to examine the effect of leverage, media exposure, profitability on carbon emission disclosure. Design/methodology/approach: This study uses a quantitative approach to analyze causal relationships by utilizing secondary data. The population of this study are companies engaged in the mining sector and listed on the Indonesia Stock Exchange during the period 2018 to 2022. The sample selection was carried out using purposive sampling method. Findings: The findings of this study reveal that leverage and media exposure have a positive and significant influence on carbon emissions disclosure, while profitability shows no significant impact. Research limitations/implications: Limitations in this study only use the mining sector during 2018-2022, so the results may not be relevant for more recent sectors or years. Reliance on reports that may be incomplete and variations in secondary data may affect the results. In addition, this study does not consider other variables or significant changes in policies and markets. Practical implications: Implications for regulators to design investment policies that promote transparency of carbon emissions, increasing investor confidence. The findings also support governments in developing regulations for cyber risk management reporting. In addition, companies can utilize the research results to identify key stakeholders, allocate resources more efficiently, and strengthen their competitive position. Originality/value: The novelty in this research can explain the determinants of carbon emission disclosure from the stakeholder perspective of the theory. Paper type: Research Paper